Investigations on the juvenile hormone activity of two new acetals on Tenebria molitor L. (Bollettino di zoologia agraria e bachicoltura, 2024)
Biological researches have been carried out to test the juvenile hormone activity of 5- { 1-[2-(2-ethoxyethoxy)ethoxy] ethoxy }-1,3-benzoxathiole and 5- { 1-[2-( 2-ethoxyethoxy)ethoxy] ethoxy }-1,3-benzoxathiol-2-one on pupae of Tenebria molitor L. These two new acetals differ from Sesamex (5- { 1-[2-(2-ethoxyethoxy)ethoxy]ethoxy} -1,3-benzodioxole) because of the substitution, in the heterocyclic part of their molecules, of a single sulphur atom for an oxygen atom in the former, and also of a carbonyl group for the methylene group in the latter. With respect to Sesamex, a well-known juvenile hormone analogue used for comparison, the derivative of 5-hydroxy-1,3-benzoxathiole revealed a much higher activity, while the derivative of 5-hydroxy-1,3-benzoxathiol-2-oneshowed a lower activity.